'The Child that is Born of One's Fair Body' – Maternal and Infant Death in Medieval Ireland. (2nd January 2021) - Murphy, Eileen M.
ABSTRACT: The paper explores the historical and archaeological evidence for maternal and infant death in medieval Ireland. An overview of a range of historical sources including law tracts, medical documents, and folklore are investigated for insights concerning the treatment of pregnant women, abortion, post-mortem caesarean, and the nature of herbs that were administered to assist with female reproductive matters. This provides the context for a review of 15 earlier and later medieval burial grounds in Ireland that produced 30 burials in which an adult female was associated with one or more foetal or perinatal infants. The individuals are considered to have potentially died as a result of obstetric complications. The overall frequency and age-at-death profiles of the women and babies are investigated. This is followed by an attempt to interpret the circumstances of each case to determine whether the death had occurred during pregnancy, childbirth or shortly after birthing.